Reflections on South African psychology with Saths Cooper. (September 2014) - Barnes, Brendon; Cooper, Saths
Saths Cooper, PhD, is an important figure in both South African and international psychology. Based on a two hour interview with Cooper, this article focuses on his experiences with Apartheid-era psychologists, his views on the abuses of psychology past and present, and his views of psychology as president of the International Union of Psychological Science. While we have much to celebrate about the 20 years of Psychological Society of South Africa's existence, Cooper's experiences are a stark reminder of the complicity of the discipline with the Apartheid state machinery. Psychology needs to remain attentive to how it is organized and applied to contemporary societal issues. It is hoped that this article will stimulate further reflections about the development of the discipline in South Africa and beyond.